Technology Entrepreneurship Project (ENT 600) : JEJE Manufacturing [M] Sdn. Bhd. / Siti Nursyuhada Baharudin - Baharudin, Siti Nursyuhada (2021)
JEJE Manufacturing is one of local plastic manufacturer that focusing in manufacture plastic bottle commercially. In this company analysis, the product that be analyse is PET water bottle that is produced by the JEJE company in order to identify the quality, marketability and imperfection of the product. Each problems faced by the company is come out with solution to improve and enhance the quality the water bottle product. The main problem of PET is non-biodegradable product that cause pollution to environment due to degradation process takes much time. It also produces endocrine disruptor, a chemical that affect the endocrine system and can cause cancer, developmental disorder, brain development problems and learning abilities. Due to the circumstances of PET plastic bottle, a solution need be adopted to make it more convince for consumption. The best one is produce the water bottle from biodegradable material which is polylactic acid (PLA). The material used is a renewable source that comes from plant. It can be degrade naturally in environment without releasing toxic materials that can be harmful.